2019
DOI: 10.1016/j.ijid.2019.03.038
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review with meta-analysis: Is ribavirin necessary in sofosbuvir-based direct-acting antiviral therapies for patients with HCV recurrence after liver transplantation?

Abstract: With the appearance of direct-acting antiviral agents (DAAs), sofosbuvir (SOF)-based DAAs are recommended for patients with hepatitis C virus (HCV) recurrence after liver transplantation (LT). Whether ribavirin (RBV) is needed by patients after LT in combination with SOF-based DAAs remains to be determined. This meta-analysis was conducted to evaluate the necessity of RBV with SOF-based DAAs for post-LT patients. Methods: PubMed, Web of Science, Cochrane Library and EMBASE databases were systematically searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Xue et al [ 193 ] reported 80% SVR 12 in 10 transplant recipients treated with SOF/RBV combination with PegIFN. The SOLAR 1 and SOLAR 2 trials reported 100% SVR 12 in 6 and 5 transplant recipients, respectively with FCH treated with SOF-LDV and RBV combination[ 119 , 120 ].…”
Section: Fibrosing Cholestatic Hepatitis (Fch)mentioning
confidence: 99%
“…Xue et al [ 193 ] reported 80% SVR 12 in 10 transplant recipients treated with SOF/RBV combination with PegIFN. The SOLAR 1 and SOLAR 2 trials reported 100% SVR 12 in 6 and 5 transplant recipients, respectively with FCH treated with SOF-LDV and RBV combination[ 119 , 120 ].…”
Section: Fibrosing Cholestatic Hepatitis (Fch)mentioning
confidence: 99%
“…Currently, there are direct-acting antiretroviral treatments for which the goal is to eliminate the virus from the body with an effectiveness rate of more than 95% depending on the genotype and co-infections. Nevertheless, high costs represent one of the main access barriers (Nápoles et al, 2019;Xue et al, 2019).…”
mentioning
confidence: 99%